Probióticos à base de Bacillus em rações de frangos de corte desafiados com Clostridium perfringens e Eimeria vacinal - Berto, Rafaela (2023)
The objective of the present study was to evaluate the use of two probiotics (Bacillus amyloliquefaciens CECT 5940: Ecobiol® and Bacillus subtilis DSM 32315: GutCare®) as a replacement for an antibiotic in the performance, carcass, and cut yields, intestinal morphometry and lesion score, blood biochemical parameters, and short-chain fatty acid (SCFA) concentration in broilers challenged with Clostridium perfringens and Eimeria vaccine. A total of 880 one-day-old Cobb 500 males (weight: 43.48 ± 0.55g) were assigned to 4 treatments with 10 replicates and 22 birds each, in an entirely randomized design.The treatments used were distributed as follows: negative control feed (NC) without the inclusion of feed additives; positive control feed (PC) + 100 g ton-1 of 8% enramycin; NC feed + 1000 g ton-1 of Ecobiol® - CECT 5940 (1.0 x 106 CFU/g of B. amyloliquefaciens BA feed); NC feed + 500 g ton-1 of GutCare® - DSM 32315 (1.0 x 106 CFU/g of B. subtilis BS feed). To induce necrotic enteritis, all birds were inoculated by gavage at 4 days of age with 20 times the dose of coccidiosis vaccine (0.6 mL/bird of Biococcivet R®) and at 7 and 10 days of age with 0.5 mL of C. perfringens culture (108 CFU/mL) isolated in the field from an outbreak of necrotic enteritis. The zootechnical parameters were determined at 28 and 42 days of age, and at 42 days, the carcass and cut yields were evaluated. The concentrations of SCFA and intestinal histomorphometry were performed at 28 days of age. The blood harvest for the evaluation of biochemical and enzymatic parameters was performed at 21 days of age. Chickens fed the NC diet had the lowest feed intake (P < 0.0001), body weight gain (P < 0.0001), and worst feed conversion (P < 0.0001) compared to the other treatments. However, the chickens fed diets BA and BS had significantly higher feed intake and body weight gain and better feed conversion compared to the birds fed the PC diet. In the duodenum, the PC, BA, and BS treatments had higher villi (P < 0.001). The PC, BA, and BS diets had higher villus height, crypt depth, and absorptive area (P < 0.001) in the jejunum compared to the NC. Supplementation with Ecobiol® - CECT 5940 (1000 g ton-1) and GutCare® - DSM 32315 (500 g ton-1) improved broiler performance relative to the antibiotic enramycin with similar intestinal morphological characteristics, while BA (1000 g ton-1) favored greater butyric acid production by the intestinal microbiota. Therefore, the use of Bacillus probiotics added to the feed was able to effectively replace the use of the antibiotic enramycin 8% under an induced intestinal challenge, with no change in the biochemical and enzymatic profile of the birds.